2020
DOI: 10.1111/obr.13094
|View full text |Cite
|
Sign up to set email alerts
|

An accountability evaluation for the responsible use of celebrity endorsement by the food and beverage industry to promote healthy food environments for young Americans: A narrative review to inform obesity prevention policy

Abstract: Research has shown that celebrity endorsement is a marketing strategy primarily used to promote highly processed food and beverage products to children and adolescents, which negatively influences their diet quality and increases their risks of obesity. This study conducted an accountability evaluation to examine government, expert, and industry policies, guidelines, recommendations, and practices regarding using celebrity endorsement to support healthy marketing environment for young Americans. This study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…Previous studies have also indicated that video formats, visual effects, and other communication forms could lead to better communication effects on video social platforms, 59 , 86 , 87 which is somewhat different from the results of this study. For young people, the knowledge and science in the videos are more critical when acquiring knowledge about the COVID-19 vaccination through social media platforms, and the form of communication does not directly affect their decision-making for vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have also indicated that video formats, visual effects, and other communication forms could lead to better communication effects on video social platforms, 59 , 86 , 87 which is somewhat different from the results of this study. For young people, the knowledge and science in the videos are more critical when acquiring knowledge about the COVID-19 vaccination through social media platforms, and the form of communication does not directly affect their decision-making for vaccination.…”
Section: Discussioncontrasting
confidence: 99%
“…In most public-private partnerships, the industry has more power and resources to influence the design and implementation of policies compared with governments. Consequently, these types of policies have been shown to have poor design and lack monitoring and enforcement mechanisms to hold the industry accountable (40)(41)(42) Therefore, the second combination of conditions that is often observed in government-led policies that are underpinned by legislation such as taxation policies (43) , statutory food marketing (44) and trans-fat bans (45) is still a better pathway to successful policies. These findings provide empirical support for food and nutrition policy recommendations made by international health organisations and the international literature (3,46) .…”
Section: Discussionmentioning
confidence: 99%
“…Johnson's general COVID-19 coverage in online news sources across 11 countries was predominantly positive (Krawczyk et al 2021), which resonates with COVID-19 and obesity coverage in UK online news (Brookes 2021). The role of celebrities has evolved from endorsements of processed food that increase obesity risks (Zhou et al 2020) to the exposure of less discussed stigmatising health topics, for example, an online survey about Carrie Fisher's, American actress, mental health advocacy in the media revealed the potential to reduce stigma (Hoffner 2020).…”
Section: Discussionmentioning
confidence: 85%